2020
DOI: 10.3390/jmse8010060
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Forcing of the Climate System in Subharmonic Modes

Abstract: During recent decades observation of climate archives has raised several questions. Concerning the mid-Pleistocene transition problem, conflicting sets of hypotheses highlight either the role of ice sheets or atmospheric carbon dioxide in causing the increase in duration and severity of ice age cycles. The role of the solar irradiance modulations in climate variability is frequently referenced but the underlying physical justifications remain most mysterious. Here, we extend the key mechanisms involving the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…He examined the idea of the modulated response of subtropical gyres to solar and orbital forcing, noting that a positive feedback loop amplifies the effects of the insolation gradient on the climate system and a resonance phenomenon occurs, filtering out some frequencies in favor of others. In another study, Pinault [56] demonstrated that the climate system in the Atlantic responds resonantly to solar and orbital forcing in several subharmonic modes. He advocated hypotheses on the evolution of the past climate, implicating the deviation between forcing periods and natural periods, according to the subharmonic modes and multi-frequency GRWs, including low frequencies.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…He examined the idea of the modulated response of subtropical gyres to solar and orbital forcing, noting that a positive feedback loop amplifies the effects of the insolation gradient on the climate system and a resonance phenomenon occurs, filtering out some frequencies in favor of others. In another study, Pinault [56] demonstrated that the climate system in the Atlantic responds resonantly to solar and orbital forcing in several subharmonic modes. He advocated hypotheses on the evolution of the past climate, implicating the deviation between forcing periods and natural periods, according to the subharmonic modes and multi-frequency GRWs, including low frequencies.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…To ensure optimum stability of the dynamic system, each period is double or triple the previous period. Each of the subharmonic numbers corresponds to the number of revolutions that the GRW travels during a period [5]. The first 11 subharmonic numbers are 9 , whose periods are the product of the number of turns by 64, namely 64, 128, 256, 768, 1536, 3072, 6144, 12,288, 24,576, 49,152, and 98,304.…”
Section: Subharmonic Modesmentioning
confidence: 99%
“…The amplitude of GRWs according to the subharmonic modes n 1 = 2 0 to n 11 essentially results from the energy transfer mechanisms between coupled oscillators, relayed by intermediate forcing when the forcing period is close to the natural period of one of the GRWs [5,9].…”
Section: Subharmonic Modesmentioning
confidence: 99%
See 2 more Smart Citations